ASSESSMENT OF THE DEVELOPMENT OF DEFORMATIONS ON THE EARTH'S SURFACE WITHIN THE STEBNYTSKY POTASSIUM DEPOSIT MINE FIELD BY THE DATA OF HYDROGEOLOGICAL SURVEILLANCE - КHEVPA, Zenon; DOLIN, Victor; YAKOVLEV, Eugene (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2023)
The paper presents the data generalization of the observations of hydrogeological monitoring of mining sites on the dynamics of groundwater level. The processing of hydro-regime studies conducted in 2009-2021 in the area of the mine bypass of the №2 pit was carried out. Hydrogeological sections reflecting changes in water levels over time were prepared. The most important factor in the lowering of the ground surface is salt karst development. The evaluation of the intensity of karst collapse processes was based on the interpretation of the results of the dynamics of the subsurface water level. The site network consists of more than 30 observation wells drilled into suprasaline and Quaternary aquifers. The main causes of deformation of the salt rock massif and the earth's surface have been identified. These are a decrease in the geomechanical strength of the rock due to its hydration and subsequent subsidence under the geostatic load of the overlying rock, and subsidence of the clay layer covering the salt rock due to the karst process. Based on the observed data, hydrogeologically oriented spatial zoning of the mining concession was performed. As a result of the development of a complex depression in the area of influence of the karst drainage, a drop in the water level in the gypsum-clay horizons was observed over the entire area in 2009-2019. The depression funnel runs in a northwesterly direction, indicating the development of a karst channel in the salts. Significant inflow of suprasaline water in the southwestern and central parts of the mine field combined with intense karstification of the salt massif and gypsum-clay cap deposits within the depression funnel resulted in significant deformation of the earth's surface, formation of karst funnels, and technogenic and ecological threats to critical infrastructure objects. To prevent a man-made ecological catastrophe, it is urgent to develop a scientific rationale for the maximum permissible changes in the environmental parameters of the man-made geological system of the №2 mine of the Stebnytsky potash deposit during the post-mining phase.
Keywords: mine processing; mine field; deformation of the earth's surface; hydrogeological wells; regime observations; flow rate of water inflow